From the “Horseshoe of Slums” to Colonias Proletarias: The Transformation of Mexico City’s “Housing Problem”, 1930–1960 - de Antuñano Emilio (Comparativ, 2020)
This article charts how housing experts dealt with Mexico City’s “housing problem” between 1930 and 1960. In the 1930s, architects and planners understood Mexico City through such North-Atlantic categories as Ernest Burgess’ concentric zone model, an approach that led them to target central “slums” as the city’s most pressing “housing problem.” But these models distorted and rendered invisible one of the city’s most original transformations: the construction of “informal” neighbourhoods in its peripheries and the fact that these neighbourhoods were, against widespread expectations, improving over time. By following a network of architects, planners, and economists working in Mexico while engaging in a broader Panamerican dialogue, I describe how Mexico City’s housing policies and ideas shifted. In the course of two mere decades, the city’s peripheral neighbourhoods went from invisible spaces to problematic and provisional settlements to a viable solution to the housing problem.